Together Towards Transparency : Lessons from the Implementation of the Construction Sector Transparency Initiative (CoST) Pilot in Guatemala - Schuster, Christian; Abreu, Anabela (2012)
Publicly financed construction is a key driver for economic growth and poverty reduction worldwide. At the same time, it is a sector unusually prone to corruption, not least due to large opportunities for rent extraction and the technical complexity of infrastructure investments. Transparency international's bribe payer's index ranks construction as the sector most likely to bribe public officials and seek state capture, and an estimated 10-30 percent of the US$5 trillion spent annually on construction worldwide is lost to corruption. Guatemala joined Construction Sector Transparency Initiative (CoST) as an associate country with support from the World Bank in November 2009. As such, it differed from pilot countries in two respects. As CoST Guatemala moves from pilot to expansion in July 2011, it is hoped that the aforementioned success factors will allow the initiative to amplify this effect-and further enhance transparency in a sector so crucial to the country's development.